Exportation of Monkeypox Virus From the African Continent. (3rd September 2020) - Mauldin, Matthew R; McCollum, Andrea M; Nakazawa, Yoshinori J; Mandra, Anna; Whitehouse, Erin R; Davidson, Whitni; Zhao, Hui; Gao, Jinxin; Li, Yu; Doty, Jeffrey; Yinka-Ogunleye, Adesola; Akinpelu, Afolabi; et al.
Abstract: Background: The largest West African monkeypox outbreak began September 2017, in Nigeria. Four individuals traveling from Nigeria to the United Kingdom (n = 2), Israel (n = 1), and Singapore (n = 1) became the first human monkeypox cases exported from Africa, and a related nosocomial transmission event in the United Kingdom became the first confirmed human-to-human monkeypox transmission event outside of Africa. Methods: Epidemiological and molecular data for exported and Nigerian cases were analyzed jointly to better understand the exportations in the temporal and geographic context of the outbreak. Results: Isolates from all travelers and a Bayelsa case shared a most recent common ancestor and traveled to Bayelsa, Delta, or Rivers states. Genetic variation for this cluster was lower than would be expected from a random sampling of genomes from this outbreak, but data did not support direct links between travelers. Conclusions: Monophyly of exportation cases and the Bayelsa sample, along with the intermediate levels of genetic variation, suggest a small pool of related isolates is the likely source for the exported infections. This may be the result of the level of genetic variation present in monkeypox isolates circulating within the contiguous region of Bayelsa, Delta, and Rivers states, or another more restricted, yet unidentified source pool. Abstract : Molecular and epidemiological data from multiple human monkeypox exportations from Nigeria show no direct linkage between travelers; however, limited genetic variation among sequenced viruses point to a possible common source pool or independently acquired infections within a small geographic area.